2016
DOI: 10.1093/infdis/jiw035
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Tuberculosis Specimen Referral Network in Uganda: The Role of Public-Private Partnerships

Abstract: Background Diagnosis of multidrug-resistant tuberculosis and prompt initiation of effective treatment rely on access to rapid and reliable drug-susceptibility testing. Efficient specimen transport systems and appropriate training on specimen referral contribute to optimal and timely access to tuberculosis diagnostic services. Methods With support and technical assistance from a public-private partnership (PPP) between Becton Dickinson and the US President’s Emergency Plan for AIDS Relief, the Uganda National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 11 publications
(8 reference statements)
1
25
0
Order By: Relevance
“…The benefits of strengthening referral systems on delays and diagnosis rates have been demonstrated in other low-income countries [35]. In Madagascar, innovative technologies such as drones were recently tested to accelerate access to diagnosis and render TB care more patient-centric by overcoming pertinent logistic barriers on the last mile [36].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of strengthening referral systems on delays and diagnosis rates have been demonstrated in other low-income countries [35]. In Madagascar, innovative technologies such as drones were recently tested to accelerate access to diagnosis and render TB care more patient-centric by overcoming pertinent logistic barriers on the last mile [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of increased proportion of specimens transported and reduced transportation time using the postal system were similar to previous studies. 15,16 Colleagues in Guinea also worked to establish a specimen referral and transport system following the West Africa Ebola virus disease outbreak, and they have documented the importance of collaborating closely with the ministry of health and conducting a baseline assessment to inform system design. 17 The specimen transport system pilot had some significant limitations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, establishment of an efficient and far-reaching specimen referral network has been explored by investigators in Ethiopia and Uganda, and shown to be effective for multiple diseases, including tuberculosis, HIV and hepatitis. 21 , 24 Therefore, establishing shared laboratory spaces, equipment and supplies, human resources and transport systems would be mutually beneficial to both tuberculosis and antimicrobial resistance programmes and improve universal access to diagnostics for the population served.…”
Section: Integration Of Laboratory Servicesmentioning
confidence: 99%